The occurrence and identification of series of organic sulphur compounds in oils and sediment extracts II. Their presence in samples from hypersaline and non-hypersaline depositional environments and possible application as source, palaeoenvironmental and maturity indicators - Sinninghe Damsté, J.S.; Rijpstra, W.I.C.; Leeuw, J.W. de; Schenck, P.A. (Pergamon, 1989)
The organic sulphur compounds (OSC) present in sixteen immature samples (both crude oils and bitumens) from different geographical locations and of different ages representing different palaeoenvironments have been analysed by GC-MS. In all samples OSC (thiolanes, thianes, thiophenes and benzo[b]thiophenes) with structures related to well-known geologically occurring hydrocarbons (n-alkanes, isoprenoid alkanes, steranes, triterpanes) occur, although the relative amounts and distribution patterns of the various OSC classes vary considerably. This variation is interpreted as a result of different sources of organic matter and different degrees of thermal maturation. The palaeoenvironments of the samples were anoxic and H₂S, produced by sulphate-reducing bacteria, probably has exceeded the input of reactive iron minerals. These conditions resulted in a surplus of free H₂S, which reacted with organic matter, leading to the formation of OSC. The distributions of OSC may be useful as molecular indicators for the assessment of sources of organic matter, palaeoenvironment and thermal maturity and for oil-oil and oil-source rock correlation studies. The distributions of the C₂₀ isoprenoid thiophenes in combination with those of the methylated 2-methyl-2-(4,8,12-trimethyltridecyl) chromans can be used to discriminate non-hypersaline from hypersaline palaeoenvironments.
Keywords: Aardwetenschappen